Nonorthogonal pulseshapes for multicarrier communications in doubly dispersive channels. - Kozek, W. (IEEE Journal on selected areas in communications)
A new approach to multicarrier digital communication over time-varying, frequency selective fading channels is presented. We propose a transmission signal set whose basic structure is similar to standard orthogonal frequency division multiple access (OFDM)-setups, i.e., a system of functions generated by time and frequency-shifted versions of a pulse-like prototype function known as a Weyl-Heisenberg (WH) system. Unlike previous OFDM studies, however, which are restricted to the case of orthonormal pulses, we consider nonorthogonal pulses that are adapted to realistically available a priori knowledge of the channel. Perfect transmultiplexing in the case of an ideal channel is incorporated as a mathematical side-constraint. We derive the expected intersymbol/interchannel interference of such a nonorthogonal FDM (NOFDM) system under the assumption of a wide-sense stationary uncorrelated scattering (WSSUS) channel. Based on this result, we compare OFDM and NOFDM schemes with regard to robustness against delay/Doppler spread